AKUNTANSI MANAJEMEN STRATEGIS SEBAGAI PENDUKUNG IMPLEMENTASI PSAK 115 DALAM MENCIPTAKAN NILAI BAGI PEMEGANG KEPENTINGAN - Hilmi Febryan; Lidya Primta Surbakti (LP2M Politeknik Jambi, 2025)
This systematic literature review examines the complex organizational transformation driven by the adoption of PSAK 115 (IFRS 15) in Indonesia, focusing on the pivotal role of Strategic Management Accounting (SMA) as a key driver and integrator. The study, based on an analysis of 20 key journal articles, finds that the shift from a rule-based to a principle-based revenue recognition standard presents significant conceptual and practical challenges, particularly in developing economies. It reveals that effective implementation and value creation extend beyond mere technical compliance, relying on a synergy of strong management control systems, adequate technological infrastructure, competent human resources, and sound corporate governance all strategically orchestrated through SMA frameworks. The findings confirm that integrating PSAK 115 with SMA facilitates not only successful implementation but also comprehensive multi-stakeholder value creation. This includes financial benefits such as improved reporting quality and reduced cost of capital, alongside non-financial gains like enhanced transparency, accountability, and stakeholder engagement. Ultimately, the research concludes that the strategic integration of PSAK 115 and SMA is a crucial investment for building sustainable competitive advantage and organizational legitimacy within Indonesia's dynamic business environment, requiring contextual adaptation of global standards to local realities.